2019
DOI: 10.1093/mny/mny048
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes matter—welfare work and migration in Sweden

Abstract: This paper investigates the factors that influence Swedish welfare workers’ attitudes towards migrants and how these attitudes are associated with their encounters with migrant users. Due to increased migration over the last decade, Sweden is now considered an immigrant nation. Migrants with the right to reside in Sweden are included within the larger welfare system. This paper argues that preconceived notions about migrants can affect the welfare services that they receive. Results from an online survey with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…As street-level bureaucrats (Lipsky, 1980), AMS employees must handle diversity-related issues when interacting with clients and are responsible for implementing migration-and integration-related policies on a local scale. Research has shown that preconceived notions held by street-level bureaucrats about migrants can affect the services they receive (Schütze, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As street-level bureaucrats (Lipsky, 1980), AMS employees must handle diversity-related issues when interacting with clients and are responsible for implementing migration-and integration-related policies on a local scale. Research has shown that preconceived notions held by street-level bureaucrats about migrants can affect the services they receive (Schütze, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Attitudes towards immigration and ethnic diversity have been topical and controversial over many decades, with studies showing both positive and negative attitudes (Holloway and Leach 2020;Novus 2014;Schütze 2020). Migration has become more important than before on the political agenda and Sweden's previous exemplary image on humanitarian policies has changed (Asztalos Morell and Darvishpour 2018;Crawley and Mcmahon 2016;Darvishpour and Westin 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 19.7% of the population is born out of Sweden and 23% have a foreign background (Statistics Sweden 2021). Sweden has a public welfare system intended to cover the entire population, including immigrants with the right to reside in Sweden (Schütze 2020). However, social exclusion of immigrants is visible; Schütze (2020, p. 425) explains, "despite this formal inclusion of migrants, many studies indicate that migrants are facing different forms of exclusion; for instance, through ethnic segregation, discrimination on the labor market and the rental housing market".…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations